2009
DOI: 10.1038/nn.2390
|View full text |Cite
|
Sign up to set email alerts
|

EFHC1 interacts with microtubules to regulate cell division and cortical development

Abstract: Mutations in the EFHC1 gene are linked to juvenile myoclonic epilepsy (JME), one of the most frequent forms of idiopathic generalized epilepsies. JME is associated with subtle alterations of cortical and subcortical architecture, but the underlying pathological mechanism remains unknown. We found that EFHC1 is a microtubule-associated protein involved in the regulation of cell division. In vitro, EFHC1 loss of function disrupted mitotic spindle organization, impaired M phase progression, induced microtubule bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 49 publications
4
73
1
Order By: Relevance
“…A significant, although faint, labeling was also observed in neocortex and piriform cortex. We have confirmed that in our recently published paper showing the expression of EFHC1 protein in E17 rat cortex (de Nijs et al, 2009). The poor expression of the signal in general does not allow a quantitative comparison with what has been observed in adulthood, although it is evident that the best pictures of nerve structures have been obtained with adult animals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A significant, although faint, labeling was also observed in neocortex and piriform cortex. We have confirmed that in our recently published paper showing the expression of EFHC1 protein in E17 rat cortex (de Nijs et al, 2009). The poor expression of the signal in general does not allow a quantitative comparison with what has been observed in adulthood, although it is evident that the best pictures of nerve structures have been obtained with adult animals.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, our previous (de Nijs et al, , 2009) and present results strongly suggest a particular function for EFHC1 in the central nervous system development. During ontogenesis of the cerebral cortex, neuronal progenitors are generated in the ventricular zone by a specialized and transient class of glial cells, the radial glial cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Five EFHC1 variants were originally reported in JME patients from Mexico 16 (P77T, D210N, R221H, F229L, and D253Y), in reverse TRPM2-induced (transient receptor potential calcium permeable M2 channel) apoptosis, and in current densities. 57 Four of these variants (the exception was P77T, which was not tested) produce severe mitotic spindle defects during cell division 55 and impair early radial and tangential migration of neuroblasts, 56 thus providing experimental evidence that EFHC1 variants are damaging to gene function. Supplementary Table S6a,b online show the published statistical results of 14 experimental measures demonstrating a significant difference between the tested variants and the wild-type protein.…”
Section: In Silico Analysis For Conservation and Damaging Effectsmentioning
confidence: 99%